Possibility of persistent current in S-states - Chanchal Yadav; Brijender Dahiya; Vinod Prasad (Scientific Reports)
Abstract In this study, we investigate the profound impact of the Pöschl–Teller double-ring-shaped Coulomb (PTDRSC) potential to induce persistent currents within the S-states of the hydrogenic atom. The confinement of the system is achieved through an impenetrable spherical boundary. Leveraging first-order perturbation theory, we quantify the charge current across various states induced by the PTDRSC potential with its inherent angular and azimuthal dependence, leading to angular and azimuthal distortion, respectively. Notably, persistent currents are observed within S-states without external excitation mechanisms. The magnitude of the induced current is intricately linked to the strength of the PTDRSC potential parameters. These results underscore the prospect of manipulating persistent currents and their associated induced magnetic fields within S-states by tailoring the potential strength and confining boundary size. This discovery presents a compelling avenue for the controlled generation and experimental verification of induced S-state magnetism, opening new possibilities for innovative applications.